Knowledge about and attitude towards COVID-19 vaccination of rural residents in Zambales, Philippines - Moncada, Romel S.; Rogayan Jr., Danilo V.; Basilio, Lyka P.; Delmita, Cherissa; Ganalon, Niño (Intelektual Pustaka Media Utama, 2024)
Vaccines are among the most effective preventive measures developed to minimize the risks of COVID-19. This cross-sectional study employs an online survey to determine the knowledge and attitude toward COVID-19 vaccination among the general population in rural Zambales, Philippines. A total of 690 residents responded to the knowledge and attitude towards COVID-19 vaccination survey questionnaire (KAC19V-SQ) regarding the residents' knowledge about and attitude towards COVID-19 vaccination. Television, Facebook and YouTube are the residents' primary sources of COVID-19 vaccine information. Almost all of them (98.0%) know about the COVID-19 vaccine, but only 81.3% of the residents know about its effectiveness. Most (69.7%) indicated they want to get vaccinated. Zambales residents' knowledge about COVID-19 vaccination was low. Despite having a low level of knowledge, respondents showed a favorable attitude (mean±SD:2.76±0.47) toward COVID-19 vaccination. Women had a less favorable attitude than men. Furthermore, a moderately positive correlation (r=0.511, p<0.01) was noted between knowledge and attitude towards COVID-19 vaccination. It is imperative that the government works in tandem with public health experts, local government officials, and academic institutions to develop and implement initiatives geared towards enhancing public awareness and fostering a positive outlook towards COVID-19 vaccination.